The usage of Facebook functional building blocks in Unisel - Abd Latib, Latifah; Bolong, Jusang; Ahmad Ghazali, Akmar Hayati (Universiti Tun Hussein Onn Malaysia, 2014)
The emergence of Internet-based social media has made it possible for a personto communicate with thousands of other people to increase the communicationeffectiveness, collaboration among internal organization and knowledge sharing.By engaging employees through social media such as Facebook as a two-waycommunications tool, employers can reach a larger audience and build credibilitywith techno-savvy workers. Although it is clear that Facebook is a very powerfultool for communication, many employers are unable to identify the functionalityof Facebook in terms of developing strategies and to allocate the resourceseffectively. Taking this into account this study sought to identify the usage ofFacebook Functionality building blocks. This survey involved 55 academic staffsfrom the Faculty of Computer Science and Information Technology, Unisel. Theseven functional building blocks identified were Identity (M=3.39), Relationships(M=3.39), Groups (M=3.6), Presence (M=3.28), Sharing (M=3.06), andConversations (M=2.90), Reputation (M=2.05). This study suggests that theability to identify the functional building blocks itself is very important in anorganization in terms of developing their communication strategies. It is hopedthat the results of the study will be applicable to the instituition, current users,and potential users of Facebook.